The Development of Constitutionalism in the Transition of Chinese Society - Cai, Dingjian (Columbia Journal of Asian Law, 2005)
China’s economy has been growing at a rate of approximately 8% annually over the last decade, and its GDP has reached about Y13.65 trillion. These dramatic economic developments have been accompanied by great changes in people’s lives, especially in the cities. In contrast to the “proletarian” status they held in the communist past, citizens now hold private interests in real property, business enterprises, and personal investments. Many people now enjoy a happier, higher quality of life than they ever knew in the past. Especially in the country’s developed regions, lifestyles and consumption patterns have reached an international standard. The achievements of China’s economic development are indeed remarkable. Nonetheless, with economic development come social problems. With a Gini coefficient recently reaching 0.5, the income gap between the haves and the have-nots in China continues to widen. In addition, unemployment plagues the Chinese economy. In some extreme cases, living conditions have not improved but have in fact deteriorated. Pressing issues of national concern include environmental destruction, stagnation-even decline-of education and public health services, and increasingly problematic issues surrounding public security in rural areas.